2011
DOI: 10.1002/pip.1135
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐enhanced light trapping in thin‐film silicon solar cells

Abstract: A systematic investigation of the nanoparticle-enhanced light trapping in thin-film silicon solar cells is reported. The nanoparticles are fabricated by annealing a thin Ag film on the cell surface. An optimisation roadmap for the plasmonenhanced light-trapping scheme for self-assembled Ag metal nanoparticles is presented, including a comparison of rearlocated and front-located nanoparticles, an optimisation of the precursor Ag film thickness, an investigation on different conditions of the nanoparticle dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 28 publications
(39 reference statements)
2
53
1
Order By: Relevance
“…This disadvantage generally exists for any sub-wavelength light trapping mechanism and it has to be overcome [7,32] . Based on these design principles, numerous computational and experimental studies have been reported on tuning the metal material, the shape, size and packing density, the dielectric environment and the position of the plasmonic nanostructures in PV devices to achieve enhanced light absorption for various types of solar cells [10,13,15,24,[31][32][33][34][35][36][37][38] .…”
Section: Guidance Direction Of Lightmentioning
confidence: 99%
See 4 more Smart Citations
“…This disadvantage generally exists for any sub-wavelength light trapping mechanism and it has to be overcome [7,32] . Based on these design principles, numerous computational and experimental studies have been reported on tuning the metal material, the shape, size and packing density, the dielectric environment and the position of the plasmonic nanostructures in PV devices to achieve enhanced light absorption for various types of solar cells [10,13,15,24,[31][32][33][34][35][36][37][38] .…”
Section: Guidance Direction Of Lightmentioning
confidence: 99%
“…The bulk recombination is so high that the surface passivation is unnecessary, and the contact between metal and the active layer only results in benefi cial near-fi eld enhancement, and does not cause noticeable performance degradation. Take one such " low quality " material, the evaporated thin-fi lm polycrystalline Si for example, the light absorption and solar cell effi ciency tend to be signifi cantly improved when the dielectric spacing layer was reduced and fi nally removed, enabling near-fi eld enhancements [24,44] . Periodic metal nanostructures on the surface of a PV device can excite surface plasmon polariton (SPP) modes.…”
Section: Local Concentration Of Light and Surface Plasmon Polaritonmentioning
confidence: 99%
See 3 more Smart Citations